A educação física na constituição do corpo poético em Jacques Lecoq - Miranda, Antonio Carlos Monteiro de (2016)
This research aimed to analyse discursively the presence of Physical Education elements in the meaning of "poetic body", in Jacques Lecoq theory, and its inscription in the International Theater School founded by the professor. Specifically the research shows the production conditions linked to the Lecoq formation in Education, Physics and Theater and studies the fundamentals and specificities of the poetic body applied in the Theater School. With an analytical character, the study was developed through publications surveys, institucional visits to the International Theater School Jacques Lecoq, in Paris, to search sources and the realization of interviews with the management and with students of the School, interviews in Brazil with former students that did their courses in the institution. The interviews aimed to know the daily reality of the School, the relations of the poetic body constitution with Physical Education and the way people realized the constitution of the poetic body, from the School context. The Speech Analysis from Michel Pecheux (1997), was the theory/method used to develop the research and to identify the researcher with his theoric and methodological basis and his destabilizing and critical potential to beyond the content to understand how it works and its meaning effects. It was found, with the research development that the poetic body proposal of Jacques Lecoq has a stong influence of Physical Education and of his time which contributes to the thesis that the poetic body theory is triggered discursively between Physical Education and Theatre. This defense occurs from the finding of the sports influences, practices and gymnastics in Lecoq pedagogy; in the body conditioning through stric disciplinary forms imposed by the School, which has to be followed with dedication by the students to be sucessful in their activities, in a kind of "conditioned" freedom; in the exemption of thought influence in the moment of the action, which is valued as an aspect of the essencial criation to the actor formation; to establish the division between theory and practice with excessive valorization of practice over theory. In this direction, the data show the contruction of a poetic body that developed between Physical Education and Theater lose the poetry to seek institutionally (in the International Theater School Jacques Lecoq); a body art focused in the conditioning, rigidity. Thoughtless production, distancing itself from the playful body, that plays and is human to the artistic make.